The morphological and grammatical structures described by virtue of goodness according to Sibawayh - Al-Fuqara, Saif Al-Dien; Alaoui, Hafid (Al-Adab Journal, 2024)
The issue of the research is that there is no special study on the rule of good in the modern linguistic lesson, despite the prevalence of this rule in linguistic studies. There are brief references to the rule of good in the studies of modern scholars without dedicating a special study to it. The research studies one of the evaluative provisions in Arabic grammar, to show the concept of this rule, its manifestations, and criteria in the linguistic lesson. The research aims to achieve a set of objectives sought from it, which is to provide a study specialized in good judgment in the language lesson through Sibawayh’s book, it includes the concept of good linguistically and idiomatically, and defines the development of its origins until the era of Sibawayh and presents the manifestations of this rule in linguistic structures. The research took the descriptive analytical approach in the research by studying the positions of good judgment in the linguistic uses of Sibawayh, and Classifying issues, studying, and analyzing them, linking them to linguistic issues, and discussing them through the contexts in which they occurred. The research reached a few results, the most important of which is rooting the term, clarifying its concept, and explaining the manifestations of its use in Arabic grammar through Sibawayh’s book. Knowing the linguistic and impressionistic controls for issuing this judgment, and knowing the criteria of Sibawayh, which balances between the linguistic uses to which this judgment applies, which were represented in the prevalence and abundance, and the observance of analogy and significance.